2020
DOI: 10.1016/j.vaccine.2020.08.053
|View full text |Cite
|
Sign up to set email alerts
|

The role of capsid in the flaviviral life cycle and perspectives for vaccine development

Abstract: Highlights The structure and function of flaviviral capsid are very flexible. The capsid gene contains conserved RNA secondary structures. Both steps of assembly and dissociation of nucleocapsid complexes are obscure. Capsid mutant viruses are highly attenuated and immunogenic. ΔC-replicon and single-round infectious particles are promising vaccine approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 98 publications
0
13
0
Order By: Relevance
“…Previous studies have shown that CP plays multiple roles in the flaviviral life cycle. Its major function is the formation of the NC core, which participates in the viral assembly process, but it is also involved in vRNA replication via conserved RNA secondary structures in the N-terminus of the capsid gene ( 12 ). Therefore, first, the RNA secondary structure of the CQW1 capsid gene was predicted via homologous modelling using RNAstructure 6.0.1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that CP plays multiple roles in the flaviviral life cycle. Its major function is the formation of the NC core, which participates in the viral assembly process, but it is also involved in vRNA replication via conserved RNA secondary structures in the N-terminus of the capsid gene ( 12 ). Therefore, first, the RNA secondary structure of the CQW1 capsid gene was predicted via homologous modelling using RNAstructure 6.0.1.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, first, the RNA secondary structure of the CQW1 capsid gene was predicted via homologous modelling using RNAstructure 6.0.1. In this model ( Figure 1A ), the first 100 nucleotides of the capsid gene are involved in the formation of SLB, 5’DAR and 5’CS, cHP and DCS-PK, and all of these cis-elements are conserved in the Flavivirus genus and are significant for vRNA replication ( 12 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DEN-2 serotype also binds with HSP70/ HSP90, GRP78, and CD14-associated protein. Both the DEN 1-3 serotypes bind to Laminin receptor bind [12,13].…”
Section: Introductionmentioning
confidence: 99%